2012
DOI: 10.1051/0004-6361/201117892
|View full text |Cite
|
Sign up to set email alerts
|

The angular momentum transport by standard MRI in quasi-Kepler cylindrical Taylor-Couette flows

Abstract: We studied the instability of a dissipative quasi-Keplerian flow influenced by a homogeneous axial magnetic field in the geometry of a Taylor-Couette system. Especially we focus on the excitation of nonaxisymmetric modes and the resulting angular momentum transport, not on dynamo action. The excitation of nonaxisymmetric modes requires higher rotation rates than the excitation of the axisymmetric mode and this the more the higher the azimuthal mode number m is. We find that the weak-field branch in the instabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…For small magnetic Prandtl numbers (here Pm = 0.01) we again find a crossing phenomenon for strong fields in the neutral-stability curves for m = 0 and m = 1 [60]. In Fig.…”
Section: Quasi-keplerian Flowsupporting
confidence: 65%
See 1 more Smart Citation
“…For small magnetic Prandtl numbers (here Pm = 0.01) we again find a crossing phenomenon for strong fields in the neutral-stability curves for m = 0 and m = 1 [60]. In Fig.…”
Section: Quasi-keplerian Flowsupporting
confidence: 65%
“…The wave numbers in Fig. 42 must be interpreted using (60) so that for kR 0 3π (horizontal dotted line) the cells are almost circular in the (R/z) plane. Below the horizontal dotted line the cells are all oblong with respect to the rotation axis.…”
Section: Influence Of Boundary Conditionsmentioning
confidence: 99%
“…By appropriately choosing the rotation ratio of the cylinders, velocity profiles of the general form w( ) r r q , including = -q 1.5 for Keplerian rotation, can be well approximated experimentally at very large Reynolds numbers (Edlund & Ji 2015;Lopez & Avila 2017). For an imposed axial magnetic field, Gellert et al (2012) found the transport coefficient α to be independent of magnetic Reynolds Rm and magnetic Prandtl Pm numbers, only scaling linearly with the Lundquist number S of the axial magnetic field. (Nornberg et al 2010), unstable magnetocoriolis waves (giving rise to the MRI) have not been reported in the literature so far.…”
Section: Introductionmentioning
confidence: 97%
“…Rotation excites the instability, but it can also be too fast for its existence. This is quite opposite to the excitation conditions of the axisymmetric (or channel) modes of standard MRI (Gellert et al 2012) or HMRI with negative shear (Stefani et al 2006;Rüdiger et al 2018a) which do not possess upper limits of the Reynolds number. The HMRI with super-rotation is thus much more stable than HMRI with sub-rotation.…”
Section: The Axisymmetric Modes In Their Dependence On the Magnetic Prandtl Numbermentioning
confidence: 58%
“…The stability maps for non-axisymmetric modes of a fluid rotating beyond the Rayleigh limit (e.g. quasi-Keplerian rotation) show for any given Lundquist number of the axial magnetic field a lower critical Reynolds number for the MRI onset and a maximal one where the diffusion stops the instability (Gellert, Rüdiger & Schultz 2012). The minimum rotation rates of the lines of neutral stability scale with Pm Re const for small Pm, and with √ Pm Re const.…”
Section: Introductionmentioning
confidence: 98%